Indonesian Breastfeed-Supporting Father: Intervensi Pembentukan Karakter Ayah Tanggap ASI di Kota Palembang - Amrina Rosyada; Dini Arista Putri; Yeni Yeni (Universitas Mathla'ul Anwar Banten, 2021)
INDONESIAN BREASTFEED-SUPPORTING FATHER: INTERVENTIONS FOR FORMING THE CHARACTER OF BREASTFEEDING FATHER IN PALEMBANG. Exclusive breastfeeding is the most effective and beneficial method for the health of mother and baby. Many factors influence the success of exclusive breastfeeding. Fathers can play a role in this but most fathers do not know the concept of exclusive breastfeeding. Some of this is due to the promotion of the health of fathers who tend not to be involved. So that this service aims to provide intervention to young fathers in order to know the concept of exclusive breastfeeding and know its role in the success of exclusive breastfeeding. Dedication was carried out in the city of Palembang in the District of Alang-alang Lebar on as many as 25 fathers. Dedication is carried out using leaflets with interesting illustrations along with explanations from enumerators. This dedication is useful to give an understanding to fathers that the wife who has just given birth does not only need material support but is also important to provide emotional support.